The Effect of Inflation, Us Dollar Exchange Rate, and Interest Rates on Gold Prices - Putri Setya Wulandari; Lidya Nova Anggraini; Bintis Ti'anatud Diniati; Billbina Elsa Cahya Agustina; Alfi Saidah (Trunojoyo University of Madura, 2026)
This study aims to analyze the simultaneous and partial influence of domestic macroeconomic indicators which include Inflation, US Dollar Exchange Rate (USD/IDR), and Interest Rate (BI-Rate) on Gold Price movements in the Indonesian domestic market. Using a quantitative approach and causal-comparative design (ex post facto), this study uses monthly secondary data for the period 2020-2024 (60 samples) which were analyzed through multiple linear regression and classical assumption tests. The results show that simultaneously, the three macroeconomic variables have a significant influence on the price of gold. However, it partially proves that only the US dollar exchange rate variable has a positive and significant influence, while inflation and local interest rates do not have a significant partial impact on domestic gold prices. This model shows a high Adjusted R Square value of 97.5%, which indicates a symptom of a long-term spurious trend typical of time-series macro data, requiring caution in interpretation. For entrepreneurs and investors, these findings show that domestic gold investment is a highly effective tool to protect capital wealth in particular from the risk of exchange rate weakness, rather than from changes in local interest rates. The study makes a new contribution by proving that the determination of domestic gold prices in the midst of extreme monetary shocks is purely driven by currency translation mechanisms, not by international safe haven competition.